Senegal : Staff Report for the 2010 Article IV Consultation, Fifth Review Under the Policy Support Instrument, Third Review Under the Exogenous Shocks Facility, Request for Waiver of Nonobservance of Performance Criterion, and Modification of Assessment Criterion; Staff Report; Debt Sustainability Analysis; Press Release; Executive Director Statement; Public Information Notice. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Article IV Consultation highlights that Senegal is pursuing its macroeconomic policies within an economic program supported by the IMF's Policy Support Instrument (PSI). Executive Directors noted that signs of a recovery have become visible, and emphasized that prudent domestic macroeconomic policies and an accelerated implementation of structural reforms would help to strengthen growth further and reduce poverty. Sustained efforts are required to enhance the financial sector's contribution to the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet